Water, sanitation, and hygiene practices mediate the association between women's empowerment and child length for‐age z‐scores in Nepal - Cunningham, Kenda; Ferguson, Elaine; Ruel, Marie T.; Uauy, Ricardo; Kadiyala, Suneetha; Menon, Purnima; Ploubidis, George B. (John Wiley & Sons, 2019)
In Nepal, more than one‐third of children are stunted. Prior studies have shown that women's empowerment in agriculture is associated with child (<2 years) length‐for‐age z ‐scores (LAZ) in Nepal. This study tests whether child dietary diversity (DD) and household water, sanitation, and hygiene (WASH) facilities and practices mediate the associations between women's empowerment and LAZ. With a cross‐sectional dataset of 4,080 households from 240 rural communities across 16 districts of Nepal, we used ordinary least squares regression models to first estimate the associations between women's empowerment and LAZ for children 6 to 24 months (n = 1,402; our previous published analysis included all children <24 months of age), using the Women's Empowerment in Agriculture Index's Five Domains of Empowerment subindex. We used standardized structural equation models to test whether child DD and/or household WASH mediated the association between women's empowerment and child LAZ. Overall, women's empowerment was positively associated with child LAZ (β = 0.24, P = 0.03), as found in our previous analyses. In the mediation analysis, women's empowerment was positively associated with WASH (β = 0.78, P < 0.001), and in turn child LAZ (β = 0.09, P < 0.001). Women's empowerment was not associated with DD, but DD was associated with LAZ (β = 0.06, P = 0.05). Empowered women had better WASH practices than nonempowered women, which translated into higher child LAZ. Child DD was not a mediating factor in the association between women's empowerment and child LAZ. More research is needed to explore other pathways by which women's empowerment may affect child nutrition outcomes.